Réponses

  • Utilisateur Brainly
2014-09-06T18:06:34+02:00
A= 5(x - 4) - 2(2x + 6)
A= 5x - 20 - 4x - 12
A= x - 32

B=(3x - 5)(5 - 2x) - 3x(x - 6)
B= 15x - 6x² - 25 + 10x - 3x² + 18x
B= - 9x² 43x - 25

C= 15y² - 25y - 25
C= 5 * 3y² - 5 * 5y - 5 * 5
C= 5(3y² - 5y - 5)

D= 3x
³ - 6x² + 18x
D= 3x * x² - 3x * x + 3x * 6
D= 3x(x² - x + 6)
2014-09-06T18:13:21+02:00
Bonjour

Développons
A= 5(x - 4) - 2(2x + 6)
 5x - 20 - 4x - 12
 x - 32

B=(3x - 5)(5 - 2x) - 3x(x - 6)
15x - 6x² - 25 + 10x - 3x² + 18x = - 9x² 43x - 25


Factorisons
C= 15y² - 25y - 25 
(5  x 3y²) - (5 x 5y) - (5 x 5) = 5 x (3y² - 5y - 5)

D= 3x
³ - 6x² + 18x 
(3x *  x²) - (3x * x) + (3x * 6) = 3x (x² - x + 6)